AIS Thredbo Alpine Training Centre (2000)
The new AIS/Thredbo Alpine Training Centre opened in September 1996 and has come at a perfect time to provide Australia and the world with an ideal alpine training camp environment. Based on a similar concept to Sierra Nevada in Spain, France's Font-Romeu and Colorado Springs in the USA, the AIS/Thredbo Alpine Training Centre provides an ideal venue for high-end sports training with state-of-the-art facilities to help trainers and athletes reach peak performance levels. Not only for the elite, the multi-purpose training centre and its full portfolio of facilities will be open to the public, clubs, schools and the local community for social and recreational activities. This summer (96/7) has seen a significant step in summer business for Thredbo with the opening of the AIS/Thredbo Training Centre. The Centre was funded to the tune of six million dollars by Kosciusko Thredbo who also staff and maintain the centre. The Institute of Sport have guaranteed to utilise the centre for the lead up to the 2000 games and offer assistance of specialised staff and equipment if required. The spring/summer/autumn seasons have been targeted for the selling of the centre with so much on offer in Thredbo in the warmer and milder months. Facility specifications Swimming Pool - Climate controlled ozonation filtration 50m swimming pool with 4 lanes x 50m and 4 lanes x 25m. Spa pool and water-slide. Squash Court - Timber sprung floor with glass back wall. Gymnasium - 170 square metre area with cushioned floor for aerobics, machine/weight training and martial arts. Sports Medicine - Access to AIS sports science, physiotherapy and massage. Indoor Sports Hall - 1600 square metre multi-purpose timber sprung floor in various configurations of court layouts: Basketball - Two full size 15 x 28m courts set end-to-end with 2m perimeter clearance Volley Ball - Two 9 x 18m courts Badminton - Seven 13.4 x 6.1m international standard doubles courts Netball - Two 30.5 x 15.25m courts, one centre court Running - 60m 4 lane running track Futsal (indoor soccer) - 35 x 20m pitch with 1m high side wall Indoor Handball - 40 x 20m international standard pitch Judo - 16 x 16m area for up to 4 mats Tennis - Two timber sprung courts with 8.1m net clearance Hockey - 43 x 24.2m clear space provided for hockey Wrestling - Ten 12 x 12m international standard mats could be laid Gymnastics - Most aspects of gymnastics could be catered for within the sports hall, equipment subject to availability. Sports Climbing - Traverse climbing wall 30m x 2.4m high.